2020
DOI: 10.1021/acsami.0c16972
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated Molybdenum Disulfide-Wrapped CdS Nanoparticles as a Nano-Heterojunction for Photo-Electrochemical Water Splitting

Abstract: We developed a heterojunction photocathode, MoS2@CdS, based on the wrapping of CdS nanoparticles by the MoS2 nanocrystals. The liquid-phase exfoliation method was adopted for preparing few-layer MoS2 nanocrystals of a layer thickness of ∼7.9 nm, whereas CdS nanoparticles of an average diameter of ∼17 nm were synthesized by the one-step hydrothermal process. The synthesized nanocrystals and nanoparticles were characterized by AFM, FESEM, HRTEM, STEM, XRD, GIXRD, UV−vis absorption, fluorescence emission, and Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Among various types of two-dimensional materials, transition-metal dichalcogenides (TMDs) have greatly captured the interests of researchers. Unique structures of S–M–S sandwiched layer, where M stands for transition-metal atoms, endow TMDs with excellent stability, sizable band gaps, outstanding photoresponse, and other fine properties, facilitating applications in gas sensing, catalysis, and electronic engineering . However, the intrinsic heavy atomic mass of transition-metal atoms and the moderate carrier mobility may limit their applications in the field of energy storage or other devices that work under light and portable scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of two-dimensional materials, transition-metal dichalcogenides (TMDs) have greatly captured the interests of researchers. Unique structures of S–M–S sandwiched layer, where M stands for transition-metal atoms, endow TMDs with excellent stability, sizable band gaps, outstanding photoresponse, and other fine properties, facilitating applications in gas sensing, catalysis, and electronic engineering . However, the intrinsic heavy atomic mass of transition-metal atoms and the moderate carrier mobility may limit their applications in the field of energy storage or other devices that work under light and portable scenarios.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Dolai et al confirmed the presence of a characteristic peak in the range of 600–800 nm in the UV analysis for the existence of nano-MoS 2 . 43 …”
Section: Resultsmentioning
confidence: 99%
“…In another study, Agarwal et al developed keratin-assisted nano-MoS 2 , wherein the formation of the nanosheets was confirmed by UV−vis analysis 19. Dolai et al confirmed the presence of a characteristic peak in the range of 600−800 nm in the UV analysis for the existence of nano-MoS 2 43. Chemical Characterization of MoS 2 .…”
mentioning
confidence: 99%
“…In order to synthesize MoS 2 , many strategies have been developed, including mechanical exfoliation, [81][82][83] solution exfoliation, [84][85][86] chemical vapor deposition [87][88][89] (CVD), hydrothermal synthesis, [90][91][92] electrodeposition methods, [93][94][95] metal-organic chemical vapor deposition (MOCVD), [96][97][98] and molecular beam epitaxy (MBE). [99][100][101] These methods can be classied as topdown methods (including mechanical exfoliation and solution exfoliation) and bottom-up methods (including hydrothermal synthesis, CVD, MOCVD and MBE).…”
Section: Synthetic Methods For Mosmentioning
confidence: 99%